2006
DOI: 10.1103/physrevlett.97.036810
|View full text |Cite
|
Sign up to set email alerts
|

Shot-Noise Signatures of 0.7 Structure and Spin in a Quantum Point Contact

Abstract: We report simultaneous measurement of shot noise and dc transport in a quantum point contact as a function of source-drain bias, gate voltage, and in-plane magnetic field. Shot noise at zero field exhibits an asymmetry related to the 0.7 structure in conductance. The asymmetry in noise evolves smoothly into the symmetric signature of spin-resolved electron transmission at high field. Comparison to a phenomenological model with density-dependent level splitting yields good quantitative agreement.Shot noise, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
87
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 27 publications
16
87
1
1
Order By: Relevance
“…This point of view is supported by magnetic focusing data obtained for the p-type device, which reveal the static spin polarisation of holes transmitted through the constriction [8]. Furthermore, recent shot-noise measurements carried out for n-type QPC [9] show that distinct transport channels exist at G < 2e 2 /h = G 0 , presumably related to spin, exhibiting quite different transmission probabilities.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…This point of view is supported by magnetic focusing data obtained for the p-type device, which reveal the static spin polarisation of holes transmitted through the constriction [8]. Furthermore, recent shot-noise measurements carried out for n-type QPC [9] show that distinct transport channels exist at G < 2e 2 /h = G 0 , presumably related to spin, exhibiting quite different transmission probabilities.…”
supporting
confidence: 60%
“…If it is so, the 1D systems may be used as an efficient spin filter with possible practical applications. This point of * Also at Instytut Fizyki Teoretycznej, Uniwersytet Warszawski, Hoża 69, PL 00-681 Warszawa, Poland; ERATO Semiconductor Spintronics Project, Japan Science Technology Agency, 1-18 Kitamemachi, Aoba-ku Sendai, 980-0023, Japan † Also at ERATO Semiconductor Spintronics Project, Japan Science and Technology Agency, 1-18 Kitamemachi, Aoba-ku Sendai, 980-0023, Japan view is supported by magnetic focusing data obtained for the p-type device, which reveal the static spin polarisation of holes transmitted through the constriction [8].Furthermore, recent shot-noise measurements carried out for n-type QPC [9] show that distinct transport channels exist at G < 2e 2 /h = G 0 , presumably related to spin, exhibiting quite different transmission probabilities.Many experiments, however, bring out rather contradictory observations regarding the temperature dependence of the additional plateau. Already Thomas and coworkers [1] revealed that the 0.7 "kink" disappears when temperature is lowered, typically below few hundreds milikelvins.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Since this theory is based on the single-particle picture, additional information such as the many-body interaction may be deduced from the precise investigation of the Fano factor combined with the conductance, as we see in the shot noise study in the Kondo regime [19][20][21][22] . Actually, the shot noise of QPC was addressed by several experimental groups; the Pauli exclusion principle was first studied, and then the quantum interference 23 , the 0.7 anomaly [24][25][26] , and the spin polarization 25,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been proposed that relate the 0.7 anomaly to a spontaneous spin splitting in zero magnetic field [5][6][7][8][9][10][11], since the 0.7 plateau evolves continuously into the spin-resolved plateau at 0.5(2e 2 /h) when an inplane magnetic field is applied. A recent theory paper [12] presented spin-density functional calculations of realistic QPC geometries that show that a localized state can exist near pinch-off in a QPC, providing a theoretical back-ground for the Kondo-like physics that was found experimentally [13].…”
Section: Introductionmentioning
confidence: 99%